Penanganan Keluhan Pelanggan dengan Sistem Aplikasi Pengaduan dan Keluhan Terpadu (APKT) pada PLN (Persero) ULP Telanaipura Jambi - Dewi, Rozlinda; Arti, Zahwa Berliana; Wahyuni, Kanthi; Suprapto, Eko (Journal of Electrical Power Control and Automation (JEPCA), 2025)
PT PLN (Persero) ULP Telanaipura showed significant improvement in overcoming customer complaints. Customers can now report their complaints practically through the PLN Mobile application or direct visits to the nearest ULP office. This efficiency is driven by the Integrated Complaints and Complaints Application (APKT), a web-based internal system at PLN. APKT is designed to process all types of complaints and grievances received from call centers 123, ensuring prompt response and resolution as per the set time standards. Prior to the implementation of APKT, complaint management was still conventional, not integrated, and without real-time monitoring. The presence of APKT has eased the workload of PLN employees throughout Jambi City rayon, allowing for faster and easier resolution of customer complaints. This study focuses on the effectiveness of the APKT system in customer complaint management at PT PLN (Persero) ULP Telanaipura. If customers have complaints, they can contact the PLN 123 call center. The customer service operator will provide guidance and gather the necessary technical information. The most dominant interference that customers often complain about is interference with the code 99110 (approximately 3.93%), which is often associated with "clear tamper" and "voltage drop" issues. In contrast, the 99115 code disruption, i.e. complaints of misinformation with unidentified causes, is very rare, accounting for only about 0.16%.